THE RELATIONSHIP BETWEEN SELF-CONTROL AND PREMARITAL SEXUAL BEHAVIOR AMONG BOARDING HOUSES AND NON-BOARDING HOUSES STUDENTS IN DKI JAKARTA - Riblita Damayanti; Eka Nia Irmayanti (Universitas Mercu Buana Jakarta, 2023)
This study aims to examine the relationship between self-control and premarital sexual behavior in boarding houses and non-boarding houses students in DKI Jakarta. The number of samples in this study were 260 students. This research sample uses a quantitative approach by using a self-control scale and a premarital sexual behavior scale. Data were analyzed using pearson correlation and comparing subjects based on residence using independent sample T-test. The results of the correlation between self-control and premarital sexual behavior show that there is a significant negative correlation between the two variables where if self-control is high then premarital sexual behavior is low, and vice versa if self-control is low then premarital sexual behavior will be high. Based on the comparative results of self-control and premarital sexual behavior in boarding houses and non-boarding houses students, it shows that non-boarding houses students have higher self-control than boarding houses students. While premarital sexual behavior in boarding houses students is higher than that of non-boarding houses students